COMMUNITY LIVING SPACE AS A FACTOR OF HUMAN CAPITAL DEVELOPMENT: CONCEPTUAL FRAMEWORK AND PRACTICAL RECOMMENDATIONS (INNOVATIVE ECONOMY, 2026)
Omelianenko O.M. COMMUNITY LIVING SPACE AS A FACTOR OF HUMAN CAPITAL DEVELOPMENT: CONCEPTUAL FRAMEWORK AND PRACTICAL RECOMMENDATIONSPurpose. The aim of the article is to consider the living space of a community as a factor in the development of human capital in order to develop proposals for the development of communities.Methodology of research. General scientific and special methods were used in the study: analysis and synthesis – to generalize scientific approaches to determining the living space of a community and its components; structural and functional analysis – to determine the relationships between the components of the living space and the development of human capital; comparative analysis – to generalize modern approaches to assessing the quality of living space; graphic method – to visualize the results of assessing the Community Accessibility Index; generalization method – to form practical recommendations for the development of communities.Findings. It was found that the living space of a community is a complex system that combines territorial and spatial, social, economic, infrastructure, institutional, cultural, security and information components. It is proven that the quality of living space directly affects the processes of formation, accumulation and realization of human capital through access to education, healthcare, digital services, economic opportunities and participation in public life. A conceptual approach to the analysis of the relationship between the living space of a community and the development of human capital through the chain: “quality of living space → conditions of everyday realization → accumulation of human capital → social and economic capacity of the community → sustainable development” is proposed.Originality. Theoretical provisions on the interpretation of the living space of a community as a multidimensional social and territorial system that determines the conditions for the development of human capital have been further developed. The approach to determining the components of the living space of a community has been improved through the integration of spatial, social, institutional, security and digital components. A conceptual model of the relationship between living space and human capital in the context of sustainable development of communities is proposed.Practical value. Substantiated theoretical and methodological provisions can be used by local governments when forming development strategies and community recovery plans.Key words: communities, living space, human capital, needs, quality of life, projects.
Keywords: communities; living space; human capital; needs; quality of life; projects